Fluid-structure interactions. Volume 1, Slender structures and axial flow - Paidoussis, M. P. (San Diego, CA : Academic Press, 1998)
This volume emphasizes the fundamentals and mechanisms giving rise to flow-induced vibration of use to researchers, designers, and operators. Fluid-Structure Interactions provides useful problem-solving tools, and conveys the ideas in a physically comprehensible manner. The book includes a complete bibliography of important work in the field. . The Non-linear behaviour of Fluid-Structure interactions . The possible existence of chaotic oscillations . The use of this area as a model to demonstrate new mathematical techniques This book will prove invaluable to researchers, practitioners, and students in fluid-structure interactions, flow-induced vibrations, and dynamics and vibrations.
Preface. Introduction. Concepts, Definitions and Methods. Pipes Conveying Fluid: Linear Dynamics I. Pipes Conveying Fluid: Linear Dynamics II. Nonlinear and Chaotic Dynamics. Curved Pipes Conveying Fluid. First-Principles Derivation of Equation of Motion. Analytical Evaluation of h2r, c2, and d3r. Destabilization by Damping. Experimental Methods for Elastomer Pipes. Timoshenko Equations and Associated Analysis. Basics of Nonlinear Dynamics. Newtonian Derivation of Nonlinear Equations. Nonlinear Analysis of a Pipe Conveying Fluid. Fractal Dimension. Derivations for Equations in Chapter 6. Matrices for an Extensible Curved Pipe. Subject Index.
Includes bibliographical references and index.
Keywords: Fluid-structure interaction; Interaction fluide-structure.; Electronic books